2007
DOI: 10.1002/jbm.a.31501
|View full text |Cite
|
Sign up to set email alerts
|

Influence of collagen‐fibril‐based coatings containing decorin and biglycan on osteoblast behavior

Abstract: Collagen is used as a scaffold material for tissue engineering as well as a coating material for implants with a view to enhancing osseointegration by mimicry of the bone extracellular matrix in vivo. The biomimicry strategy can be taken further by incorporating the small leucine-rich proteoglycans (SLRPs) decorin and biglycan, which are expressed in bone. Both bind to fibrils during fibrillogenesis in vitro. In this study, the ability of collagen types I, II, and III to bind decorin and biglycan was compared.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 75 publications
0
33
0
1
Order By: Relevance
“…Arrows indicate the orientation of the substrate topography to a specific location. Glycosaminoglycans and proteoglycans [95][96][97] or bioactive molecules such as growth factors or hormones are traditionally used to enhance biological functions of biomaterials [98][99][100][101]. However, such molecules are typically labile; the biologic half-lives of plateletderived growth factor, basic fibroblast growth factor, and vascular endothelial growth factor are 2, 3, and 50 min, respectively, when intravenously administered [102].…”
Section: Discussionmentioning
confidence: 99%
“…Arrows indicate the orientation of the substrate topography to a specific location. Glycosaminoglycans and proteoglycans [95][96][97] or bioactive molecules such as growth factors or hormones are traditionally used to enhance biological functions of biomaterials [98][99][100][101]. However, such molecules are typically labile; the biologic half-lives of plateletderived growth factor, basic fibroblast growth factor, and vascular endothelial growth factor are 2, 3, and 50 min, respectively, when intravenously administered [102].…”
Section: Discussionmentioning
confidence: 99%
“…Douglas et al have shown the ability of several collagens to bind small leucine-rich proteoglycans and glycosaminoglycans (GAGs), and these interactions were not the same. [1][2][3] Tsai et al have shown that polysaccharides can be used to vary the reconstitution rate, fiber size, and morphology of collagen. 4) Human hematopoietic stem cells have been cultivated on collagen-coated film with heparin and with hyaluronic acid.…”
mentioning
confidence: 99%
“…Composites in the present study used a polymeric matrix of natural COL not only to achieve a stable composite and to prevent rapid release of calcium ions in surrounding medium [20], but to improve the interaction with osteoblast cells. It is known that COL has binding sites that promote cell attachment through focal contacts and adhesion plaques, providing an increased cell adhesion capacity to composites designed for bone regeneration [35].…”
Section: Discussionmentioning
confidence: 99%